An adjustable decoding scheme for robust and efficient transmission in FTTR C-WAN architecture - Chen, Zhihao; Peng, Fuzhou; Chen, Xiang (2023 International Conference on Microwave and Millimeter Wave Technology (ICMMT), 2023)
This paper investigates an effective adjustment scheme of the LDPC decoding algorithm according to the channel states in the Fiber-to-the-Room (FTTR) system with Centralized/Cloud Wireless-optical Access Network (C-WAN) architecture. The family scenarios of Distributed-MIMO (D-MIMO) channels of 5GHz Wi-Fi are measured and analyzed. According to the proposed scheme, the gain brought by the C-WAN architecture is transformed to the decrease of computation and time complexity of LDPC algorithm, which matches burst transmission character of Wi-Fi system. Simulations and experiments show that D-MIMO technology certainly improves the performance of family network system and an average 3dB gain of Signal-to-Noise ratio (SNR) is achieved. When using the Offset Min-Sum (OMS) algorithm, the LDPC decoding performance can approach the Belief Propagation (BP) algorithm at lower complexity, which also can improve the throughput of LDPC by reducing the number of iterations.